Squeezing the bears: Cornering risk and limits on arbitrage during the 'British Bicycle Mania', 1896-1898 - William Quinn (Queen's University Centre for Economic History (QUCEH), 2016)
Can limits to arbitrage explain historical asset price reversals? During the "British Bicycle Mania" of 1896-1898, cycle share prices rose by 200 per cent before falling 76 per cent from their peak value. This paper argues that arbitrage during this episode was limited by the risk of being cornered after short selling shares. Three corners in cycle company shares occurred during the "mania", two of which resulted in substantial losses for short-sellers. The first corner corresponded with a structural break in cycle share prices, and crosssectional analysis reveals that companies for which cornering risk was greater experienced more pronounced mispricing.
Keywords: G19; N23; 330; market corner; short selling; bicycle mania